PENGARUH PEMBERIAN ASI DAN STIMULASI PSIKOSOSIAL TERHADAP PERKEMBANGAN SOSIAL-EMOSI ANAK BALITA PADA KELUARGA IBU BEKERJA DAN TIDAK BEKERJA - Eva Latifah; Dwi Hastuti; Melly Latifah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2010)
The aims of this research were to know characteristics of family and child who come from family whose working mother and unworking mother; to analyze the differences of breastfeeding and psychosocial stimulation between two groups; to analyze the correlation between characteristics family and child, with breastfeeding and psychosocial stimulation; and to analyze the impact of breastfeeding and psychosocial stimulation toward child’s social-emotion development. A cross sectional design was applied in this research. This research represented the part of Yuliati’s (2006) research which entitled “Study of behavior buying and consuming milk for 2-5 years old of child and impact to child’s growth and development”. Population in this research represented sample from Yuliati’s research that were selected by purposive with criteria 3,5-5 years old of children who come from family whose working mother and unworking mother. The result showed that there were not significant differences between characteristics of family and child, duration of breastfeeding and psychosocial stimulation between two groups. Correlation test of Rank Spearman showed that only father’s education and family’s income that had significantly negative correlation with duration of breastfeeding. Meanwhile, father’s education, mother’s education, family’s income and mother’s knowledge about child’s growth and development significantly had positive correlation with psychosocial stimulation. Based on gender, girl significantly had higher psychosocial stimulation than buy. Psychosocial stimulation and child’s age were dominant factor in influencing child’s social-emotion development, while duration of breastfeeding was not influencing.